Influence of dispersant application on the toxicity to sea urchin embryos of crude and bunker oils representative of prospective oil spill threats in Arctic and Sub-Arctic seas. (November 2021) - DeMiguel-Jiménez, Laura; Etxebarria, Nestor; Lekube, Xabier; Izagirre, Urtzi; Marigómez, Ionan
Abstract: This study deals with the toxicity assessment of crude and bunker oils representative of prospective oil spill threats in Arctic and Sub-Arctic seas (NNA: Naphthenic North-Atlantic crude oil; MGO: Marine Gas Oil; IFO: Intermediate Fuel Oil 180), alone or in combination with a third-generation dispersant (Finasol OSR52®). Early life stages of sea urchin, Paracentrotus lividus, were selected for toxicity testing of oil low-energy water accommodated fractions. A multi-index approach, including larval size increase and malformation, and developmental disruption as endpoints, was sensitive to discriminate from slight to severe toxicity caused by the tested aqueous fractions. IFO (heavy bunker oil) was more toxic than NNA (light crude oil), with MGO (light bunker oil) in between. The dispersant was toxic and further on it enhanced oil toxicity. Toxic units revealed that identified PAHs were not the main cause for toxicity, most likely exerted by individual or combined toxic action of non-measured compounds. Graphical abstract: Unlabelled Image Highlights: Heavy bunker oil is more toxic than light marine diesel and naphthenic oil. The third generation dispersant Finasol OSR52® is toxic to sea urchin embryos. LEWAF toxicity was enhanced in three studied oils after dispersant addition. Identified individual PAHs are not the main cause for oil toxicity.